Pengaruh Fraud Hexagon Terhadap Kecurangan Laporan Keuangan Perusahaan Properti dan Real Estate - Riswana, Indi Citra; Saharsini, Astuning; Pardi, Pardi (Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital, Ekonomi Kreatif, Entrepreneur (JEBDEKER), 2023)
Through the use of the F-score model approach, this study aims to determine the variables of financial stability, external pressure, personal financial needs, ineffective monitoring, nature of industry, change in director, change in auditor, frequency of CEO picture and political connection in influencing fraudulent financial reporting. The research sample was obtained through a sampling technique using the purposive sampling method of 20 companies from 85 companies in the property and real estate industry sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The research data is in the form of secondary data obtained from the company financial reports and company annual reports sourced from the Indonesia Stock Exchange (IDX) website www.idx.co.id and the website of the secretariat of the Republic of Indonesia cabinet setkab.go.id in obtaining information on political ties between companies with government. The data analysis method in this study uses multiple linear regression analysis with the help of the IBM SPSS 25 analysis tool. The results of this study indicate that the change in auditor variable has a significant effect on fraudulent financial reporting while the financial stability variables, external pressure, personal financial needs, ineffective monitoring, nature of industry, change in director, frequency of CEO picture and political connection have no significant effect on fraudulent financial reporting.